Resection and anastomosis in one stage due to colon occlusion: Extraperitoneal and subcutaneous anastomosis. Extramucosal monoplane suture - Perrone, Luis; Suaya, Hadel; Paperán, Juan; Laviña, Raúl; González Moreno, Yamandú; Pérez Penco, Enrique (Cirugía del Uruguay, 1979)
Case material consists of 5 primary excissions of left occluded colon. Measures for restoring transit during acute phase consisted of termino-terminal anastomosis and extramucosa monoplane suture utilizing 5/0 monofilament, located in an extraperitonear subcutaneous tunnel. Thus the danger of fecaloid peritonitis due to suture fail ure is nil. It is also useful in preventing the multiple operations and morbimortality of colostomies.